Host Serine Proteases: A Potential Targeted Therapy for COVID-19 and Influenza - Rahbar Saadat, Yalda; Hosseiniyan Khatibi, Seyed Mahdi; Zununi Vahed, Sepideh; Ardalan, Mohammadreza (Frontiers in Molecular Biosciences, 2021)
The ongoing pandemic illustrates limited therapeutic options for controlling SARS-CoV-2 infections and the need for additional therapeutic targets. The viral spike S glycoprotein binds to the human receptor angiotensin-converting enzyme 2 (ACE2) and then is activated by host proteases. Based on the accessibility of cellular proteases needed for SARS-S activation, SARS-CoV-2 entrance and activation can be mediated by endosomal (such as cathepsin L) and non-endosomal pathways. Evidence indicates that in the non-endosomal pathway, the viral S protein is cleaved by the furin enzyme in infected host cells. To help the virus enter efficiently, the S protein is further activated by the serine protease 2 (TMPRSS2) provided that S has been cleaved by furin previously. In this review, important roles for host proteases within host cells will be outlined in SARS-CoV-2 infection and antiviral therapeutic strategies will be highlighted. Although there are at least five highly effective vaccines at this time, the appearance of viral mutations demands the development of therapeutic agents. Targeted inhibition of host proteases can be used as a therapeutic approach for viral infection.